The Importance of Social Connectedness in Building Age-Friendly Communities. (24th November 2011) - Emlet, Charles A.; Moceri, Joane T.
Abstract : The purpose of this paper is to further elucidate the importance of social relationships and social connectedness with aging in place and in developing elder-friendly communities. The process used in this study was inclusive of younger adults (age 40–65) as well as older adults (65+) in order to further understand how they envision a community that could support their own aging in place. A community forum, using the World Café format, was conducted in order to engage community members, 40 years and older, in conversation about the importance of social connectedness in elder-friendly communities. A second purpose of this forum was to obtain data on what would keep aging boomers in their community as they age. Three major themes emerged from qualitative analysis of the forum: social reciprocity, meaningful interactions, and structural needs/barriers . The results of this study reinforce the importance of social connectedness in creating and maintaining elder-friendly communities for older adults, as well as soon-to-be retired individuals, wishing to maintain life connectedness to their community. The study suggests the possibility of using more nontraditional research techniques (such as the World Café process) for gathering community level data.